2015
DOI: 10.5433/1679-0359.2015v36n1p203
|View full text |Cite
|
Sign up to set email alerts
|

Use of castor meal (Ricinus communis L.) as a source of dietary protein in goats during the mating period: impact on reproductive and metabolic responses

Abstract: Use of castor meal (Ricinus communisL AbstractThe aim of the present study was to evaluate the effects of the total substitution of soybean meal with castor meal, detoxified or non-detoxified, on the response to estrous synchronization, conception rate, early fetal development, presence of IgG, and metabolic-hormonal response. Sixty mixed goats were fed diets without castor meal (WCM), with detoxified castor meal (DCM), and with castor meal (CM) during early pregnancy. The goats had their estrous synchronized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Further it was also observed that there was no significant (P>0.05) difference in progesterone concentration among the ewes fed conventional diet (S1) and complete feed blocks (S2 and S3). These results are in agreement with previous studies [ 21 , 22 , 36 ], who reported that there was no effect on progesterone profile by replacement of conventional protein supplements with unconventional protein supplements like detoxified castor seed meal or DDGS or Nigella Sativa meal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further it was also observed that there was no significant (P>0.05) difference in progesterone concentration among the ewes fed conventional diet (S1) and complete feed blocks (S2 and S3). These results are in agreement with previous studies [ 21 , 22 , 36 ], who reported that there was no effect on progesterone profile by replacement of conventional protein supplements with unconventional protein supplements like detoxified castor seed meal or DDGS or Nigella Sativa meal.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the present findings, Silva et al . (2015) [ 36 ] also observed no significant (P>0.05) effect on gestation length, lambing rate and litter size when ewes fed the castor seed meal or detoxified castor meal. Abdalla et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on effects of using detoxified castor bean cake in animal feed, especially on spermatogenesis. However, some studies evaluated the reproductive performance of females and suggested that using detoxified castor bean cake does not change the reproductive performance in sheep and goats (Silva et al, 2014;Silva et al, 2015). These reports corroborate the results of present study, which showed that using detoxified castor bean cake did not affect spermatogenesis in sheep.…”
Section: Discussionsupporting
confidence: 89%
“…One of the alternative to reduce the cost of animal feed is via the use of byproducts of biofuel production. Silva et al (2015) proposed castor beans to be one of the most suitable oilseeds for the production of biofuel in northeastern Brazil, because of their ability to produce in water shortage, can be used in consortium with other crops, and in family farming production systems, besides being popular with consumers and therefore having high market value. Sub-products of castor bean obtained after oil extraction can potentially be used in the preparation of animal feed, because of their considerable protein content, low cost, and ease of use (Sousa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it can be detoxified with calcium oxide replacing up to 50% of soybean meal in lambs' diet [127] and reducing the production costs in a beef cattle grazing system [130]. Furthermore, up to 15% non-detoxified CB meal can be used in goat feed [131]. Castor bean can also be considered an ecofriendly and economic alternative to synthetic insecticidal agents (e.g., against Spodotpera frugiperda, Spodoptera littoralis, Musca domestica, and Phlebotomus duboscqi, the Leishmania vector) [132][133][134][135].…”
Section: Castor Bean Productsmentioning
confidence: 99%